074 In vivo cell tracking of superparamagnetic iron oxide-labelled mononuclear cells in humans. (22nd September 2015) - Richards, J M J; Shaw, C A; Lang, N N; Semple, S I; Crawford, J H; Mills, N L; Dhaliwal, K; Simpson, A J; Burdess, A; Roddie, H; McKillop, G; Atkinson, A P; et al.
Abstract : Introduction: Stem cell and other cell-based therapies have emerged as promising novel treatment options for acute myocardial infarction and heart failure. Ascertaining whether cells reach and remain in the target site is essential to monitor the success of these therapeutic strategies. We have developed a Good Manufacturing Practice (GMP)-compliant protocol for labelling monocytes with an MRI contrast agent (Endorem, Guerbet) containing superparamagnetic particles of iron oxide (SPIO), and evaluated the potential for its use for human cell tracking studies. Method: Up to 10 9 human peripheral blood mononuclear cells were labelled with SPIO using protamine sulphate as a transfection agent. In vitro labelling efficiency, viability and migratory capacity were evaluated. Six healthy volunteers each received intramuscular thigh injections of labelled cells (10 7 ), unlabelled cells (10 7 ) and SPIO alone, and underwent T2-weighted (T2W) MRI (1.5T) immediately and 7 days later. Safety of intravenous infusion was determined using a phased-dosing protocol in which two volunteers each received six doses of cells (10 4 –10 9 cells). Six further volunteers received 5×10 7 SPIO-labelled cells intravenously, and underwent serial T2 and multiecho (TE 4.1–22.1 ms) T2*-weighted imaging (3 T) before and serially after administration of cells. Imaging focused on the liver and spleen since this was where cells were expected to accumulate in healthy volunteers in the absence of an inflammatory focus. Results: An optimised labelling protocol maximised SPIO uptake without affecting viability or migratory capacity. SPIO-labelled cells were visualised on T2W imaging following intramuscular administration (Abstract 74 Figure 1 ). Intravenous administration of up to 109 labelled cells was well tolerated with no effect on coagulation parameters. Reduction in signal intensity was seen in the liver and spleen on T2W imaging (Abstract 74 Figure 2 ) and a significant reduction in T2* value (Abstract 74 Figure 3 ) was observed in the liver (p<0.01) and spleen (p<0.001) following intravenous administration of cells, reflecting accumulation of SPIO-labelled cells at these sites. Conclusions: We have shown that up to 10 9 human mononuclear cells can be labelled with SPIO under GMP-compliant conditions without affecting cell viability or migratory capacity. Intramuscular and intravenous administration of up to 10 9 SPIO-labelled cells is safe, and we have demonstrated for the first time in humans that SPIO-labelled cells can be imaged at a target site following local or systemic administration. Key to the success of cell-based studies, we have demonstrated the operational capacity of our institution to deliver a study of this nature. This pilot work enables us to progress to clinical cell tracking studies in patients with advanced atherosclerotic disease.